The Association Between Leucine and Diabetic Retinopathy in Different Genders: A Cross-Sectional Study in Chinese Patients With Type 2 Diabetes - Li, Shen; Huang, Bing; Liu, Ming-Li; Cui, Xue-Ting; Cao, Yun-Feng; Gao, Zheng-Nan (Frontiers in Endocrinology, 2022)
Objective: To explore the association between serum leucine (leu) and diabetic retinopathy (DR) in patients with type 2 diabetes (T2D); to analyze the influence of gender on the association meanwhile. Method: Electronic medical records of 1149 T2D patients who met inclusion and exclusion criteria were retrieved from the Second Affiliated Hospital of Dalian Medical University and the first Affiliated Hospital of Jinzhou Medical University. Plasma leu levels of all subjects were measured by liquid chromatography-mass spectrometry. According to the purpose of the study, logistics regression was used to obtain the odds ratio (OR) and confidence interval (CI) of leu-DR risk in multiple models. When using these models, restricted cubic spline (RCS) was used to test the potential nonlinear relationship between multiple continuous independent variables such as leu and DR (classification) dependent variables. We also used additive interaction method to evaluate the interaction effect between leu and gender on DR. Results: leu was a protective factor of DR (0.78(0.66,0.92)). When divided gender into male and female, the above relationship was statistically significant only in males (0.73(0.58,0.94)). Three indicators of additive interaction RERI、AP、S suggested that there is no interaction between gender and leu on the risk of DR. Conclusions: Male T2D patients with high leu levels may have a lower risk of DR.